One of the world’s worst economic collapses, now compounded by the Ukraine crisis: What’s next for Lebanon? - Breisinger, Clemens; Khouri, Nadim; Glauber, Joseph W.; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
High food prices and supply disruptions triggered by the Russia-Ukraine war are hitting Middle Eastern and North African (MENA) countries like Egypt, Sudan, and Yemen hard, partly due their heavy dependence on wheat imports. But in the region, Lebanon — already in the midst of one of the world’s worst economic collapses since the 1850s — is uniquely vulnerable to food security impacts from the Russia-Ukraine conflict. A recent World Bank report calls Lebanon’s current crisis “The Great Denial” — referring to an ongoing breakdown of government services, civil society, and the economy.